Mechanical behavior of wood subjected to mode II fracture, using an energetic criterion: Application on THUJA of Morocco - Amal Saoud; Abdelhamid Elamri; Khadija Kimakh; Mohsine Ziani; Moussa Elmatar (Fracture and Structural Integrity)
Shear strength is one of the properties often used to qualify a wood species for use in industry. But until now there is no standardized test which allows understanding this phenomenon. This paper constitutes a new approach to study the behavior of the wood material subjected to the mode II fracture. For that we designed and realized a new prototype of a wooden specimen that we tested in our laboratory which gives rise to an evaluation of the fracture until separation by pure shear of the specimen in the TL plane. The experimental data from a first series of tests on Thuja wood (Tetraclinis Articulata (Vahl) Masters) as a test material as well as the calculation of mode II initiation fracture toughness and the critical stress intensity factor are presented in this paper.